Fossil future why global human flourishing requires more oil, coal, and natural gas--not less - Epstein, Alex. (2022 Penguin)
What does the future hold? In Fossil Future, Epstein, applying his distinctive ?human flourishing framework? to the latest evidence, comes to the shocking conclusion that the benefits of fossil fuels will continue to far outweigh their side effects?including climate impacts?for generations to come. The path to global human flourishing, Epstein argues, is a combination of using more fossil fuels, getting better at ?climate mastery,? and establishing ?energy freedom? policies that allow nuclear and other truly promising alternatives to reach their full long-term potential.
Includes bibliographical references and index.
Keywords: Fossil fuels--Social aspects